Description of Macronutrient Intake and Infectious Diseases Among Stunted Children in the Working Area of Kamal Health Center, Bangkalan Regency - Ashalya Eka; Inne Soesanti; Juliana Christyaningsih; Taufiqurrahman Taufiqurrahman (Journal of Nutrition Explorations, 2025)
Background: Stunting in toddlers is primarily caused by inadequate macronutrient intake and repeated infections. This study aims to describe the intake of macronutrients and the history of infectious diseases among stunted toddlers in the working area of Kamal Health Center, Bangkalan Regency. Methods: A descriptive cross-sectional study was conducted involving 25 stunted toddlers. Stunting status was assessed using height-for-age z-scores. Data on macronutrient intake (energy, protein, fat, carbohydrates) and history of acute respiratory infections (ARI) and diarrhea were collected through structured interviews with caregivers. The data were analyzed using frequency and percentage distributions. Results: Most subjects were girls (52%) and aged 24–36 months (36%). Energy intake deficits were found in 72% of toddlers, protein in 84%, fat in 76%, and carbohydrates in 68%. All respondents had experienced at least one ARI episode, and 56% had a history of diarrhea. Many children with infections also had light to moderate macronutrient deficits. Conclusion: Chronic deficits in energy and protein, combined with frequent infections, exacerbate the risk of stunting. Integrated nutrition and infection control interventions—especially for children aged 24–36 months—are essential. Strong policy support and improved parental education are needed to implement effective stunting reduction programs at the community level.